Fibroblast growth factor receptor (FGFR) gene amplifications are rare events in bladder cancer. Issue 5 (12th January 2015) - Fischbach, Anna; Rogler, Anja; Erber, Ramona; Stoehr, Robert; Poulsom, Richard; Heidenreich, Axel; Schneevoigt, Birte‐Swantje; Hauke, Sven; Hartmann, Arndt; Knuechel, Ruth; Veeck, Jürgen; Gaisa, Nadine T
<x xml:space="preserve">Abstract</x> Aims Activating point mutations and protein overexpression of fibroblast growth factor receptors (FGFRs), especially FGFR3, are frequent events in bladder cancer. Little is known about gene amplifications, therefore we characterized amplification of FGFR1‐3 by fluorescence in‐situ hybridization (FISH). Methods and results Tumours of 153 patients (n = 65 pTa low‐grade, n = 15 pTa high‐grade, n = 37 pT1, n = 20 pT2, n = 10 pT3, n = 6 pT4) were analysed by FISH for FGFR1‐3 copy numbers and screened for FGFR3 mutations and immunohistochemical protein expression. Amplifications of FGFR1 were found in 1.6% (two of 122), FGFR2 in 0.8% (one of 121) and FGFR3 in 3.4% (five of 145). All amplifications were high‐level amplifications, not overlapping with polysomy. Amplifications were found in papillary/papillary‐invasive tumour parts, and predominantly in tumours with enhanced Ki67 index (>10%), aberrant CK20 expression, and low p53 expression. All FGFR3‐amplified samples showed concomitant FGFR3 mutations and FGFR3 protein overexpression. FGFR amplifications were not associated significantly with gender, age, grade or stage in statistical analyses. Conclusions FGFR amplifications are rare events in bladder cancer, with FGFR3 amplification being the most prevalent (3.4% of cases). Concomitant FGFR3 mutations and protein overexpression indicate that FGFR3‐mediated signalling in these tumours would probably be highly active. This patient subgroup may be particularly suited to FGFR‐targeted pharmacotherapy.